2015
DOI: 10.1039/c5ta06575e
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial oxide ion migration in scheelite-type electrolytes: a combined neutron diffraction and computational study

Abstract: W-doped LnNbO4+d compounds (Ln = La, Nd) have been recently proposed as novel interstitial-based oxide ion conductors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 56 publications
2
27
0
Order By: Relevance
“…For example, when trivalent La 3+ ions are partly substituted for Pb 2+ site of PbWO 4 , oxide ion interstitials are created as Pb 1-x La x WO 4+x/2 to exhibit a high oxide ion conduction at elevated temperature. [3][4][5] Similar enhancement in ionic conduction due to the oxide ion interstitials has been reported for other scheelite-type structured systems, such as PbMoO 4 , 6 CaMoO 4 , 7 BaMoO 4 , 8 high-temperature form of CeNbO 4 , 9 LaNbO 4 , 10,11 or GdNbO 4 . 12 However, CaWO 4 with mineral name of scheelite is unlikely to form solid solution by lanthanum substitution incorporating excess oxide ions at interstitial site.…”
Section: Accepted M Msupporting
confidence: 65%
“…For example, when trivalent La 3+ ions are partly substituted for Pb 2+ site of PbWO 4 , oxide ion interstitials are created as Pb 1-x La x WO 4+x/2 to exhibit a high oxide ion conduction at elevated temperature. [3][4][5] Similar enhancement in ionic conduction due to the oxide ion interstitials has been reported for other scheelite-type structured systems, such as PbMoO 4 , 6 CaMoO 4 , 7 BaMoO 4 , 8 high-temperature form of CeNbO 4 , 9 LaNbO 4 , 10,11 or GdNbO 4 . 12 However, CaWO 4 with mineral name of scheelite is unlikely to form solid solution by lanthanum substitution incorporating excess oxide ions at interstitial site.…”
Section: Accepted M Msupporting
confidence: 65%
“…7,21 The fergusonitescheelite transition temperature is decreased by W 6+ doping, with the x ¼ 0.16 sample appearing almost tetragonal at room temperature. 23 The presence of interstitial oxide ions in LNWO also leads to modulated ordering schemes 24,25 similar to those observed in Ce 4+ -doped CeNbO 4+d . 26 Oxide ion mobility is facilitated in LNWO via an interstitialcy mechanism that probably incorporates both interstitialframework and interstitial-interstitial jumps.…”
Section: Introductionmentioning
confidence: 57%
“…Thus, for the functionality of the given nano-SrMoO 4 sensing material used at high temperature, oxygen diffusion from lattice and interstitial sites are required for the redox reaction. It is known that scheelite oxides have the ability to include high concentrations of stable interstitial oxygen ions within its structure, and previous research has shown that this leads to a compensating mechanism to enhance structural stability under low oxygen partial pressure environments at high temperature [78][79][80][81][82].…”
Section: So 2 Sensor Testing Of the Nano-srmoo 4 And Post-mortem Analmentioning
confidence: 99%